2014
DOI: 10.1007/s10562-014-1384-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Temperature Programmed Desorption of Hydrogen from Polycrystalline Copper

Abstract: Temperature programmed hydrogen desorption (H 2 -TPD) is a versatile tool to characterize metal surfaces in heterogeneous catalysts. We present a systematic H 2 -TPD study combined with a kinetic analysis of the H 2 desorption process from pure polycrystalline copper and alumina supported copper. The results show that, in contrast to typical Cu/ZnO based methanol synthesis catalysts, the alumina support has no measureable influence on the desorption process and that the copper surface in both catalyst can be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Although this technique has often proved the linear correlation between surface area and activity in methanol synthesis, it fails to provide a correct interpretation of structure-function relationships for catalytic systems with strong Cu-ZnO interactions (i.e. where SMSI -strong metal support interaction-effects occur) [4][5][6]. Recently the presence of a "graphite-like" ZnOx overlayer decorating the Cu particles in fresh and spent high-performance catalysts was clearly demonstrated by Lunkenbein et al [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although this technique has often proved the linear correlation between surface area and activity in methanol synthesis, it fails to provide a correct interpretation of structure-function relationships for catalytic systems with strong Cu-ZnO interactions (i.e. where SMSI -strong metal support interaction-effects occur) [4][5][6]. Recently the presence of a "graphite-like" ZnOx overlayer decorating the Cu particles in fresh and spent high-performance catalysts was clearly demonstrated by Lunkenbein et al [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of this CO 2induced poisoning is most likely the poor activity of ZnO for H 2 activation that could regenerate the required oxygenvacancies and drive the reaction. Copper is significantly better at activating H 2 as had been show by Muhler et al 322,323,458 This long held aspect of the chemistry leads to a principal reason for the synergetic behavior. Copper is the main source for adsorbed H* species that are required to hydrogenate adsorbed CO 2 to formate and consequently to methanol.…”
Section: The State Of Zinc In the Operating Czamentioning
confidence: 75%
“…456 The results of this study, which specifically relate to the gas adsorption properties of the catalyst, are presented in Figure 72. They found that as the hydrogen pressure of the 411,458 were also added. (b) Same plot type for a variety of supported copper samples using different reduction methods.…”
Section: Conclude: "[T]here Is a Relationship Between The N 2 O-rfc S...mentioning
confidence: 99%
“…Because the TPD behavior seen in this temperature range is similarly independent of the presence or absence of coadsorbed N 2 H 4 , we conclude that by this temperature all species resulting from hydrazine adsorption and decomposition may have desorbed from the surface, and that the hydrogen produced may predominantly originate from formic acid decomposition. It should also be noted that hydrogen production in this case is reaction limited, as the production and desorption of H 2 from hydrogen-saturated Cu(110) takes place at much lower temperatures, around 300–350 K. …”
Section: Resultsmentioning
confidence: 92%